If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = 15 + -4x Solving 2y = 15 + -4x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 7.5 + -2x Simplifying y = 7.5 + -2x
| X^4+6x^3-x^2-24x+16=0 | | 3x^2y^2=0 | | x*x-2x[1+3m]+7[2+3m]=0 | | 16t^2+18t+24=0 | | 4x^3-12x=00 | | X^2+4x=3x^2+4x+2 | | (x-50x/3)^2 | | 700x(45x*23)=0 | | (X-1)(X-3)(X-4)= | | 2x^3-5x^2-2x+4=0 | | 15s=3s | | 10y=11x-6 | | 2-5+7*6=x | | 3(x-(1))+5(x-(1))(x-(3))+(x-(1))(x-(3))(x-(4))= | | y=28-2x | | 3-12*4=x/4 | | 4y/3=2y/8 | | 6s+39=207 | | x+(x+98.75)=368.75 | | -3x+ax=b+-6 | | 2+6x-4=2 | | (13-1)/(14/14) | | ax-3x=b-6 | | n+4-9=5 | | 4(3X-9)+1=25 | | liman=4n^2+3n-2 | | 3a-5=11-5a | | 15x=10y+40 | | y=(1x+1)*(0.1x+1)*(0.75x+1)*(0.75x+1)+1 | | -4(2x+2)=6 | | y=(1x+1)*(0.1x+1)*(0.75x+1)*(0.75x+1) | | 9(-2x+2)=8 |